2018
DOI: 10.1097/ijg.0000000000001019
|View full text |Cite
|
Sign up to set email alerts
|

Goniotomy Using the Kahook Dual Blade in Severe and Refractory Glaucoma: 6-Month Outcomes

Abstract: Goniotomy with trabecular meshwork excision using the KDB could be an alternative surgery for severe or refractory glaucoma, significantly reducing IOP and medication use at 6 months, with a low rate of complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
65
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(79 citation statements)
references
References 31 publications
8
65
3
Order By: Relevance
“…The IOP reductions seen in this study are consistent with a prior study of stand-alone goniotomy with the KDB in eyes with severe and refractory glaucoma, in which mean IOP reductions of 24% were observed, medication reduction was 36.6%, and nearly 60% of eyes achieved a minimum 20% IOP reduction [14]. These results also compare favorably with other blebless, stand-alone, ab interno procedures.…”
Section: Discussionsupporting
confidence: 89%
“…The IOP reductions seen in this study are consistent with a prior study of stand-alone goniotomy with the KDB in eyes with severe and refractory glaucoma, in which mean IOP reductions of 24% were observed, medication reduction was 36.6%, and nearly 60% of eyes achieved a minimum 20% IOP reduction [14]. These results also compare favorably with other blebless, stand-alone, ab interno procedures.…”
Section: Discussionsupporting
confidence: 89%
“…As shown in previous studies, having experienced surgeons to train residents in a new surgical technique has been beneficial in reducing complications in the operative setting. 14,18 Additionally, residency wet-laboratory workshops, review of surgical videos prior to cases, and close supervision from attending surgeons may also lead to more efficient surgical time management while maintaining low complication rates. 19 Microhyphema, or suspended red blood cells in the anterior chamber, is an expected observation in the first 2 weeks following phaco-KDB due to blood reflux from Schlemm's canal, 10 and often does not affect the final IOP or best corrected vision.…”
Section: Discussionmentioning
confidence: 99%
“…5,7, 9,10 Intraoperative or postoperative anterior chamber blood reflux is common and expected as with any Schlemm's canal bypassing procedures, 12,13 but this generally resolves in the first postoperative week without additional intervention. 10,14 As the surgical treatment of glaucoma continues to increase, the demand for well-trained ophthalmic surgeons who are capable of performing glaucoma procedures will continue to grow. As such, increasing numbers of comprehensive ophthalmologists are beginning to incorporate MIGS into their practice, 15 as well as the potential for a stronger emphasis to be placed on incorporating MIGS into the training curriculum for ophthalmology residency programs.…”
mentioning
confidence: 99%
“…Morales et al, with Phaco-ECP, reported the results obtained for IOP lowering to 15 mmHg and report an absolute success of 11.9% with a quali ed success of 72.3% 14 . A retrospective Brazilian study on 247 patients, de ned success based on IOP 21mmHg with 3 years of follow-up reported the corresponding rates were 55.7% for absolute success and 90.7% for quali ed success 15 .…”
Section: Cataract Extraction As a Stand Alone Procedures Does Not Provmentioning
confidence: 99%